2015
DOI: 10.1002/hed.24282
|View full text |Cite
|
Sign up to set email alerts
|

Histologic assessment of tumor budding in preoperative biopsies to predict nodal metastasis in squamous cell carcinoma of the tongue and floor of the mouth

Abstract: Tumor budding using immunohistochemistry for cytokeratin should be added to routine histologic assessments as a new criterion factoring into the decision as to whether neck dissection is indicated. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1582-E1590, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(128 citation statements)
references
References 33 publications
(82 reference statements)
11
109
0
4
Order By: Relevance
“…In oral cancer, few studies have evaluated tumor budding as a prognostic factor or risk factor for lymph node metastasis, with only three studies reviewing the evaluation of both histopathological depth and tumor budding. Based on a study of 91 patients with oral cancer, Seki et al suggested that a histopathological tumor depth ≥ 3 mm and a budding score ≥ 3 were associated with lymphatic metastasis, and this cutoff point offered a NPV and sensitivity of 100% with high PPV and specificity [35]. Their study included patients with floor of mouth and advanced cancer, such as T3/4, who received preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oral cancer, few studies have evaluated tumor budding as a prognostic factor or risk factor for lymph node metastasis, with only three studies reviewing the evaluation of both histopathological depth and tumor budding. Based on a study of 91 patients with oral cancer, Seki et al suggested that a histopathological tumor depth ≥ 3 mm and a budding score ≥ 3 were associated with lymphatic metastasis, and this cutoff point offered a NPV and sensitivity of 100% with high PPV and specificity [35]. Their study included patients with floor of mouth and advanced cancer, such as T3/4, who received preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate evaluation of these features is difficult in preoperative biopsy specimens or intraoperative frozen sections. Seki et al compared tumor depth and budding score in biopsies with those in resected specimens in 44 patients with untreated oral cancer [35]. A good correlation was observed for budding score, but not for tumor depth.…”
Section: Discussionmentioning
confidence: 99%
“…The number of tumor buddings has negative correlations with the degree of tumor differentiation. There are more tumor buddings in minimally differentiated CRCs than in the highly differentiated and moderately differentiated CRCs [57, 6265]. In clinical practice, Dukes staging system has been widely used for CRC classification for many years because it can effectively predict the disease prognosis.…”
Section: Tumor Budding and Its Clinical And Pathologic Significancesmentioning
confidence: 99%
“…Similar results on the significance of tumor budding were reported in an independent cohort of hypopharyngeal SCC by Imai et al, 11 and also for pharyngeal SCC by Karpathiou et al 34 Specifically, identification of high intensity of tumor budding in HNSCC has been associated with metastasis to cervical lymph nodes. 40 The aforementioned findings strongly indicate that tumor budding is a histopathologic marker eligible for the evaluation in tumor samples and to be implemented in routine pathology reports of many subsites of HNSCC, and to be considered in treatment planning. 11,35 Tumor budding was also associated with advanced N classification in a recent study on laryngeal and pharyngeal SCCs.…”
Section: Tumor Budding As a Simple Promising Prognostic Marker In Hmentioning
confidence: 98%